Study on stability and bearing characteristics of macroscopic pressure arch of surrounding rock in western deep buried stope of China - Yang, Yuliang; Zhao, Yixin; Ma, Jianqi; Han, Penghua (Frontiers in Earth Science, 2023)
In view of the obvious loose and weak occurrence characteristics of the deeply buried thick weakly cemented stratum in the western mining area of China, the bearing characteristics and stability mechanism of the macrography surrounding rock pressure arch (SRPA) are studied. Firstly, considering the engineering characteristics of deep mining, a SRPA model with trapezoidal load was constructed based on the three-hinged arch theory, the shape characteristic, rise-span ratio and arch thickness equations were derived, the arch thickness under different stress paths is analyzed to characterize the bearing performance of pressure arch. Secondly, the internal force distribution law and destabilization damage type were studied by establishing a two-dimensional bearing SRPA model through arch without articulation theory. The instability type and location can be accurately judged and verified by simulation of similar materials. The results show that, the rational arch axis of SRPA is a cubic parabola with opening downward, its rise-span ratio is between 0.3 and 0.5. Increasing the rise-span ratio and lateral pressure coefficient can promote the stable bearing capacity of arch. Axial force distribution on the SRPA section is basically consistent with the arch axis, and the arch has the best bearing characteristics. The positive bending moment occurs in the ranges of [0°, 30°] and [81°, 90°] on both sides of the symmetry axis, where is prone to tensile failure. The maximum shear force is concentrated on the arch waist and skewback, and these sections are prone to shear failure. The instability modes of SRPA can be divided into “skewback—vault (arch waist)” and “vault (arch waist)—skewback”. The research results have theoretical guiding significance for mining roof management.